Polimorfismo da Long Terminal Repeat (LTR) do HIV-1 em amostras do sul do Brasil - Silva, Lourenco Moises Pereira da Costa Teixeira da [UNIFESP] (2016)
Upon cell entry, reverse transcription of genomic RNA of HIV-1 and the core input of the complex pre-integrative viral DNA is then integrated into the cell host genome. The transcription of HIV-1 provirus is regulated by various transcription factors that interact with the regulatory elements of LTR region that are involved in trans-activation of identical LTR. There are two LTRs, each located at one end of the provirus of HIV-1. Each LTR is divided into three regions: U3, R and U5A U3 region is divided into three elements: promoter, enhancer, and modulatory region and contain important binding sites for cellular proteins that regulate viral transcription levels. The R region contains the tat responsive element (TAR) that functions as an enhancer for binding to the viral protein trans-activator of transcription (Tat - transactivator of transcription) and is essential in the production of viable viral transcripts. Another important region is the U5 which contains binding sites for cellular transcriptional factors that are important for viral infectivity. The high genetic diversity of HIV-1 is due to the high viral replication rate, the high mutation rate, insertions, deletions and genetic recombination events. Binding sites in the LTR have been described in various subtypes of HIV-1. In HIV-1 subtype C there is greater possibility of duplication factor Nf-kB and increased virulence by increasing transcription and viral replication, thus presenting the form duplication of NF-kB appears more effective than the native form without duplication. This study aimed to confirm the presence of duplication most commonly in HIV-1 subtype C and clarify if the variability in the LTR can influence the efficiency of viral transcription and could contribute to virulence of different subtypes and recombinant forms. A total of 15 samples from a group of patients presenting recent infection from southern Brazil, from a testing center of Rio Grande do Sul, where is expected to find high prevalence of subtypes of interest to the study (C, B and F). The LTR fragments were determined by nested PCR and direct sequencing using specific primers. After sequencing and editing, the sequences were analyzed phylogenetically. In this study, we found predominantly subtypes B, C and F, confirming the literature data. Duplication of NF-kB appears predominantly associated with the subtype C. However, there was no statistical significance when comparing sequences with no duplication or replication of NF-kB, according to HIV subtypes or viral load.